Commitment from Government of Assam (India) to scale a combined intervention to improve food safety in informal dairy and pork value chains - CGIAR Research Program on Agriculture for Nutrition and Health (2020)
The World Bank and Government of Assam have co-invested US$262 million to scale a food safety intervention designed and tested by ILRI in informal dairy and pork value chains.